2013
DOI: 10.1108/lht-01-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Cost and benefit of quality control visual checks in large-scale digitization of archival manuscripts

Abstract: Purpose – The purpose of this paper is to provide much needed data to staff working with archival digitization on cost and benefit of visual checks during quality control workflows, and to encourage those in the field of digitization to take a data-driven approach to planning and workflow development as they transition into large-scale digitization. Design/methodology/approach – This is a case study of a cost benefit analysis at the Triangle Research Libraries Network. Data were tracked on time spent perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…If the archivist or the responsible person is not scanning exactly according to the agreements in the quotation and the test, errors in the execution of the technical specifications or in the giving of filenames of the scans or the OCR can still be adjusted in an early stage. This quality control is essential and is in first instance done by the quality manager (Chapman and Leonard, 2013). The people who do the quality control must be particular about the process since it will link to the good result of the material.…”
Section: Produce Quality In Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the archivist or the responsible person is not scanning exactly according to the agreements in the quotation and the test, errors in the execution of the technical specifications or in the giving of filenames of the scans or the OCR can still be adjusted in an early stage. This quality control is essential and is in first instance done by the quality manager (Chapman and Leonard, 2013). The people who do the quality control must be particular about the process since it will link to the good result of the material.…”
Section: Produce Quality In Resultsmentioning
confidence: 99%
“…Then, the good equipment such as automated check that will be able to handle by the staff and with a lot of practice it will improve their skills and techniques. By the skills they have, they can use any kind of technique to produce a good quality material (Chapman and Leonard, 2013) Improve preservation strategies When doing quality control, the preservation strategies can be improved. This is because the quality control requires proper and double checking about the content of the materials right after the scanning (Chapman and Leonard, 2013).…”
Section: Improve Staff Techniques Methods and Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study involved cost benefit analysis at the Triangle Research Libraries Network to determine whether quality control visual checks were cost efficient in large-scale digitization projects. The results showed that 85 percent of the time was spent scanning and 15 percent on quality control with visual scans of all items (Chapman and Leonard 2013). Only 0.4 percent of scans had errors, and only 0.1 percent had critical errors; production could have increased by 18 percent if the quality control checks had not been performed, and this would have had little effect on the overall quality of the project (Chapman and Leonard).…”
Section: Cost Benefitmentioning
confidence: 99%